2009
DOI: 10.1088/0022-3727/42/14/145406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dispersion on the increased relative permittivity of TiO2/SEBS composites

Abstract: Polymer composites are currently suggested for use as improved dielectric materials in many applications. Here, the effect of particle size and dispersion on the electrical properties of composites of rutile TiO2 and poly(styrene–ethylene–butadiene–styrene) (SEBS) are investigated. Both 15 and 300 nm particles are mixed with SEBS, with amounts of sorbitan monopalmitate surfactant from 0 to 3.3 vol%, and their dielectric and mechanical properties are measured. Composites with the 300 nm TiO2 particles result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 20 publications
4
57
1
1
Order By: Relevance
“…This notable decrease in permittivity can be explained by a change in the interphase properties of the SEBS/TiO2 composite. Similar results were concluded from a study conducted by McCarthy et al [17]. …”
Section: Dielectric Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…This notable decrease in permittivity can be explained by a change in the interphase properties of the SEBS/TiO2 composite. Similar results were concluded from a study conducted by McCarthy et al [17]. …”
Section: Dielectric Analysissupporting
confidence: 92%
“…In particular, for nanocomposites fabricated with TiO2 [17] and BaTiO3 [22], researchers found that simple mixing rules applies and the experimental results matched the theoretical ones [15,16] [24]. At low levels, an increase in filler volume fraction leads to an increase in permittivity, but to a decrease in the breakdown strength by over 50%, resulting in a decrease in the electrostatic energy density [17].…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations